Effectiveness of Healthy Food Management Based on Christian Culture Mandates in Moderamen GBKP Kabanjahe, Tanah Karo District - Mulyono, Sri (the International Journal of Education, Theology, and Humanities, 2023)
The world's population continues to grow at a rapid pace. Efforts to provide food for the world's population must be a common agenda, not only sufficient in number, but also healthy. Moderamen GBKP Kabanjahe through the Alpha Omega Disabled Welfare Foundation (YKPC) has made efforts to manage healthy food. Coffee commodity is a favorite type of food to be developed. The following problems are still found: (a) there is no collective awareness of the dangers of using chemical elements in healthy food management, (b) the work is done by children with special needs, so the results are not optimal, (c) the magnitude of the potential and market opportunities for Coffee commodity needs cannot be utilized for maximum economic improvement. Agrosocioecopreneur (Asep) is a solution offered for healthy food management at YKPC Alpha Omega. This research uses a qualitative descriptive method. The purpose of this study was to examine the effectiveness of healthy food management based on the Christian Cultural Mandate at Moderamen GBKP Kabanjahe. The findings in this study are as follows: (a) understanding and understanding of the environment in its sustainability has been well understood, (b) food production and management in an environmentally sustainable manner has not been fully implemented, the indicator still uses chemical elements by 50%, (c) food production has not been oriented towards the implementation of agropreneur, (environmentally friendly results, able to encourage new entrepreneurship actors, market rejuvenation with current technology), (d) empowerment of people with disabilities is an effort to restore their dignity and character, so that it is possible to minimize social problems in society, but it will not be effective for large-scale production, (e) there is a master plan for utilizing and maintaining the environment as an economic activity through ecowista and ecoeducation.